IMPLEMENTATION OF PERFORMANCE-BASED BUDGETING IN IMPROVING REGIONAL EXPENDITURE EFFICIENCY: LITERATURE REVIEW - Cut Meliza Saputri; Widya Wati; Eka Nurmala Sari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Performance-based budgeting is a planning, budgeting and evaluation system that emphasizes the relationship between the budget and the desired results. Budgeting with this performance approach is prepared with an output orientation. The success of a government organization does not only depend on how the organization carries out its daily processes and activities, but also depends on how routine and non-routine activities are sequenced within a strategic planning framework. Strategic planning is a key word that will provide direction and guide daily activities and activities. The performance of the Regional Government can be measured through the evaluation of the implementation of the APBD. For this reason, Cost Analysis Standards, performance benchmarks, and cost standards were developed. The most important reason for preparing an annual budget is the need to determine the level of income and expenditure (expenditure)